Characterization of surface-oxides on char under periodically changing oxidation/desorption conditions. (March 2021) - Cerciello, Francesca; Coppola, Antonio; Lacovig, Paolo; Senneca, Osvalda; Salatino, Piero
Abstract: A novel experimental method based on periodic swinging of oxidation/desorption reaction stages is used to investigate the formation and release of surface oxides on carbon under mild oxidation conditions. The chemical nature of the carbon-oxygen complex and the key mechanistic features of the interaction between solid carbon and oxygen are assessed by continuous monitoring of CO/CO2 release during the experiments and by probing - via XPS - the chemical nature of oxygen moieties at different stages of the experiments. Sub-bituminous char is used as carbon substrate. The proposed technique turns out to be a simple though effective method to assess the nature and extent of surface oxides formed under different reaction conditions. Results show that oxygen is extensively chemisorbed on carbon as epoxy moieties below ~750 K. At higher temperatures, isomerization into "edge" oxides (ether-hydroxyl and carbonyl-carboxyl functionalities) takes place, followed by oxide decomposition and desorption as CO and CO2 . Estimates of the oxygen chemisorption rate as a function of temperature are given. The study provides new insights into the extent and chemical nature of surface oxides on carbons, that represent one key to their successful application in several areas of energy conversion and storage. Oxides affect surface physico-chemical (polarity, wettability) and electrical (capacitance, resistivity) properties, relevant to application of carbons in batteries, supercapacitors and fuel cells. Moreover, understanding surface oxides on carbon is helpful in designing novel concepts of energy conversion from carbon through chemical looping, transient operation of stationary combustors, synthesis of carbon-based catalysts, beneficiation of ash. Graphical abstract: Image 1 Highlights: Characterization of surface oxides on carbon generated by mild oxidation. Novel experimental technique based on swinging of oxidation/desorption stages. Excellent correlation between XPS and dynamic oxidation/desorption experiments. CO/CO2 release by desorption reflects the abundance of edge versus epoxy oxides. Relevant to tailoring of carbons for energy and environmental applications.